2018
DOI: 10.1016/j.wear.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the occurrence of a wavy wear track on elastomeric materials

Abstract: Elastomeric materials are used in daily applications, such as tires and conveyor belts. Sliding friction of elastomeric materials often produces a unique periodic wear pattern. In general, the periodic wear pattern has to be prevented because it generates surface instabilities and, as a result, vibration. Sliding contact between an elastomer and a rigid ball may cause the development of a periodic wear pattern like a wave on the elastomer surface, called a wavy wear track. The present study has investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…It indicates that the test results according to Figures 4 and 5 confirm the analytic equations in Equations ( 2) and (3). Moreover, the wear pattern spacing obtained is longer for a larger deadweight [10,21,26]. In short, the wear pattern spacing depends not only on the given deadweight but also on the indenter system properties.…”
Section: Wear Pattern Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…It indicates that the test results according to Figures 4 and 5 confirm the analytic equations in Equations ( 2) and (3). Moreover, the wear pattern spacing obtained is longer for a larger deadweight [10,21,26]. In short, the wear pattern spacing depends not only on the given deadweight but also on the indenter system properties.…”
Section: Wear Pattern Analysismentioning
confidence: 87%
“…Identification of the wear pattern spacing has also been theorized as a stick-slip theory that the length of the pattern spacing does not only depend on the static load on the indenter but also depends on dynamic load due to the oscillating motion of the indenter and its frame along abrasion. Based on the formula, this stick-slip theory is applicable to various types of indenter tip [20,21]. Experimentally, it has also been shown that there is a correlation between pattern spacing length and abrasion rate [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, research on friction contacts in tire rubber has been widely carried out by some researchers. Many valuable results were obtained from the research, both on the prototype scale and laboratory scale [2][3][4][5]. The parameters produced are generally in the form of friction force, friction coefficient and abrasion wear.…”
Section: Introductionmentioning
confidence: 99%
“…Most of rubber or elastomer friction has been studied experimentally in sliding contact. There were some valuable results associated with a friction contact, i.e., friction force, stick-slip occurrence, abrasion wear etc [3][4][5][6][7]. Experimentally, when a smooth rubber surface was abraded, a periodic wear pattern was formed i.e.…”
Section: Introductionmentioning
confidence: 99%